ANALISIS PROGRAM ADIWIYATA PADA EKOLITERASI SISWA KELAS IV DI MADRASAH IBTIDAIYAH 1 KABUPATEN KARANGANYAR - Mahendra, Moefty; Dewi, Sri Utami; Ramdani , Ajang (Jurnal Dikdas Bantara, 2023)
This research aims to: (1) Describe the implementation of the Adiwiyata program at MIN 1 Karanganyar. (2) Describe the ecoliteracy abilities of class IV MIN 1 Karanganyar students. This research method uses a qualitative method with a descriptive approach. The research subjects were 13 class IV students. Data collection techniques were taken through observation, interviews and documentation. The data analysis technique uses qualitative data analysis techniques. The data validity technique uses triangulation techniques. The results of the research can be concluded that the analysis of the Adiwiyata program on the ecoliteracy of class IV students at MIN 1 Karanganyar is: (1) There are several programs implemented as recipients of the Adiwiyata School award. Programs that are still routinely implemented include waste banks, ecobricks, green houses and environmentally friendly activities. But currently the green house program is no longer running smoothly due to lack of funds. (2) The ecoliteracy abilities of class IV students at MIN 1 Karanganyar show that they still need to be improved in the head and heart aspects. What is still a concern is that in the head aspect, students have not been able to show their ecoliteracy because in the sub-chapter on sorting waste, most students do not have the habit of sorting waste. Even though almost all students were able to name and differentiate between types of organic and inorganic waste, they seemed indifferent and did not pay attention to the waste sorting activity. As for the heart aspect, students have also not been able to demonstrate their ecoliteracy skills because there are still some students who claim to like picking flowers in the garden or school garden, this certainly does not reflect empathy for plants. Not only that, there are still some students who don't dare to reprimand their friends when they throw rubbish carelessly, such as in drawers. Meanwhile, in the hands aspect, students are able to demonstrate ecoliteracy through the correct use of cleaning tools, are able to demonstrate the habit of bringing supplies from home as a solution to reduce the impact of the problem of plastic waste accumulation, and students are able to demonstrate an attitude of saving electricity and water at school.